TETHYAN, MEDITERRANEAN, AND PACIFIC ANALOGUES FOR THE NEOPROTEROZOIC-PALEOZOIC BIRTH AND DEVELOPMENT OF PERI-GONDWANAN TERRANES AND THEIR TRANSFER TO LAURENTIA AND LAURUSSIA - Keppie J.D.; Nance R.D.; Murphy J.B.; Dostal J. (My University, 2003)
Modern Tethyan, Mediterranean, and Pacific analogues are considered for several Appalachian, Caledonian, and Variscan terranes (Carolina, West and East Avalonia, Oaxaquia, Chortis, Maya, Suwannee, and Cadomia) that originated along the northern margin of Neoproterozoic Gondwana. These terranes record a protracted geological history that includes: (1) ∼1 Ga (Carolina, Avalonia, Oaxaquia, Chortis, and Suwannee) or ∼2 Ga (Cadomia) basement; (2) 750–600 Ma arc magmatism that diachronously switched to rift magmatism between 590 and 540 Ma, accompanied by development of rift basins and core complexes, in the absence of collisional orogenesis; (3) latest Neoproterozoic–Cambrian separation of Avalonia and Carolina from Gondwana leading to faunal endemism and the development of bordering passive margins; (4) Ordovician transport of Avalonia and Carolina across Iapetus terminating in Late Ordovician–Early Silurian accretion to the eastern Laurentian margin followed by dispersion along this margin; (5) Siluro-Devonian transfer of Cadomia across the Rheic Ocean; and (6) Permo-Carboniferous transfer of Oaxaquia, Chortis, Maya, and Suwannee during the amalgamation of Pangea. Three potential models are provided by more recent tectonic analogues: (1) an “accordion” model based on the orthogonal opening and closing of Alpine Tethys and the Mediterranean; (2) a “bulldozer” model based on forward-modelling of Australia during which oceanic plateaus are dispersed along the Australian plate margin; and (3) a “Baja” model based on the Pacific margin of North America where the diachronous replacement of subduction by transform faulting as a result of ridge–trench collision has been followed by rifting and the transfer of Baja California to the Pacific Plate. Future transport and accretion along the western Laurentian margin may mimic that of Baja British Columbia. Present geological data for Avalonia and Carolina favour a transition from a “Baja” model to a “bulldozer” model. By analogy with the eastern Pacific, we name the oceanic plates off northern Gondwana: Merlin (≡Farallon), Morgana (≡Pacific), and Mordred (≡Kula). If Neoproterozoic subduction was towards Gondwana, application of this combined model requires a total rotation of East Avalonia and Carolina through 180° either during separation (using a western Transverse Ranges model), during accretion (using a Baja British Columbia “train wreck” model), or during dispersion (using an Australia “bulldozer” model). On the other hand, Siluro-Devonian orthogonal transfer (“accordion” model) from northern Africa to southern Laurussia followed by a Carboniferous “Baja” model appears to best fit the existing data for Cadomia. Finally, Oaxaquia, Chortis, Maya, and Suwannee appear to have been transported along the margin of Gondwana until it collided with southern Laurentia on whose margin they were stranded following the breakup of Pangea. Forward modeling of a closing Mediterranean followed by breakup on the African margin may provide a modern analogue. These actualistic models differ in their dictates on the initial distribution of the peri-Gondwanan terranes and can be tested by comparing features of the modern analogues with their ancient tectonic counterparts.
Keywords: Analogues; Neoproterozoic–Paleozoic birth; Peri-Gondwanan terranes; Paleozoic; Precambrian::Proterozoic::Neoproterozoic; Палеозой; Докембрий::Протерозой::Неопротерозойская